ADMISSION ANGIOGRAPHIC CEREBRAL CIRCULATION TIME MAY PREDICT SUBSEQUENT ANGIOGRAPHIC VASOSPASM AFTER ANEURYSMAL SUBARACHNOID HEMORRHAGE - Udoetuk, Joshua D.; Stiefel, Michael F.; Hurst, Robert W.; Weigele, John B.; LeRoux, Peter D. (Neurosurgery, 2007)
Abstract OBJECTIVE Angiographic cerebral vasospasm occurs in approximately 70% of patients hospitalized after aneurysmal subarachnoid hemorrhage (SAH) and is associated with poor outcome. In this study, we examined whether or not cerebral circulation time (CCT) measured with digital subtraction angiography was associated with angiographic vasospasm. METHODS Patients who underwent cerebral angiography within 24 hours of SAH were analyzed. Contrast dye transit time from the arterial to the venous phase was measured to obtain CCT (supraclinoid internal carotid artery to parietal cortical veins) and microvascular CCT (cortical middle cerebral artery to parietal cortical veins). Patients with ruptured anterior circulation aneurysms and vasospasm on follow-up angiography (Group A) were compared with patients with SAH without vasospasm (Group B) and with normal control subjects (Group C). RESULTS There were 20 patients in Group A (mean age, 51 ± 13 yr), 17 patients in Group B (56 ± 12 yr), and 98 patients in Group C (52 ± 12 yr). CCT in patients in Group A (7.7 ± 1.9 s) was significantly longer than those in Groups B (6.6 ± 1.2 s; P = 0.005) and C (5.9 ± 1 s; P < 0.001). Microvascular CCT in patients in Group A (7.1 ± 1.8 s) was significantly longer than those in Groups B (6.1 ± 1.2 s; P = 0.003) and C (5.4 ± 0.9 s; P < 0.001). CONCLUSION Prolonged CCT, a measurement of increased small vessel resistance, can be identified within 24 hours after SAH and is associated with subsequent angiographic vasospasm. These results suggest that microcirculation changes may be involved in vasospasm.